Secure and Reliable Transfer of data in Wireless Body Area Network - Sidhanshu Mahajan, Er. Prabhsharan Kaur (International Journal of Advanced Science and Technology, 2020)
Wireless sensor network (WSN) is a technology which is contributed in various fields like healthmonitoring, field management, surveillance etc. Due to advancement in sensors one of the emergingtechnologies that is Wireless Body Area Network (WBAN) which is a subset of WSN and it iscontributing so much in day to day life of person health. The sensors in WBAN are implementing on,in and around the body which will help in monitoring the health of a person remotely. A person canavail these services using various wireless communication devices. Some of concerns which has to beconsider are Secure transfer of personal data in wireless channel, efficient management of sensor byconsidering different scenarios such as power consumption, network topology etc. The underneathpaper elaborates different techniques and frameworks for network management and secure transfer ofdata